Making Soap from Coconut Oil and Canola Oil for Asman Toga Temulawak in Singopadu Village, Tulangan District, Sidoarjo Regency - Fitroh Annisaul Mubarokah; Nandyta Rizqy A; Sudiana Putri; Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Mandira Cendikia, 2024)
One way to prevent skin problems is by bathing with soap after daily activities. Soap can help remove dirt, dust, and sweat from the body completely. The basic ingredients for making soap are fatty acids and alkali. The fatty acids used can be obtained from animals and plants such as coconut oil and canola oil. Both are useful for producing stable foam and producing soap that protects the skin and moisturizes it. This community service aims to train the community or Asman Toga Temulawak group of Singopadu Village in making soap from the herbal ingredients they produce. The methods used in this service are lecture, demonstration and practice together. The results of this community service activity show that the participant or the Asman Toga Temulawak group in Singopadu Village are really enjoyed, excited and enthusiastic about participating in this training because they could make bar soap products from herbs with attractive packaging and then market them as new products from Asman Toga Temulawak.